Pengaruh Sanitasi dalam Kandang Sapi terhadap Total Bakteri Susu Sapi Perah di KAN Jabung Malang - Dewi Kartika Sari Wijayan Daru; Ahmad Syauqi; Majida Ramadhan (IKIP Budi Utomo Malang, 2022)
The purpose of this study was to study the effect of environmental sanitation in cowshed by farmers in the working area of KAN Jabung on the total bacteria in dairy cows' milk. This research method uses a descriptive method with repeated observations during the period of the sanitation process. Sanitation of the cage environment is carried out, namely the process of washing the cage using clean water. In observing the sanitation of the cage using an assessment sheet, it includes three components of requirements, namely: the location of the cage, the direction of the cage and the technical construction of the cage with supporting data, such as frequent illness of livestock. Testing for total bacteria in dairy cow's milk uses the TPC (Total Plate Count) test with data on average quality grades in morning milking milk. To find out the difference in the effect of sanitation from the three regions, the One-way Anova test was used. Meanwhile, to test the comparison of the average difference of the three regions using Duncan's test. The results showed that there was a significant effect in three areas of the cage between environmental sanitation in the cowshed on the total bacteria in the milk of dairy cows. The total mean bacteria from milked milk is ± 5.7 x 105 CFU/ml and meets the first grade of SNI. The type of water used for cage sanitation is thought to affect the total microorganisms in milk.